The Relationship Between Parental Attachment And Student Discipline At Mts Nurul Huda Sedati - Septian Dwi Mursini; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2017)
This research is a correlational quantitative method that is motivated by phenomena that seek to undiscipline in school environment. This study aims to determine whether there is a relationship between parents with discipline students in MTs Nurul Huda Sedati. Variables in this research is Parent attachment as independent variable (X) and Discipline as independent variable (Y). This research was conducted in MTs Nurul Huda Sedati covering class VII-IX with total sample of 221 students, taken using proporsionate stratified random sampling technique. Data collection in this research using psychological model that is Likert, that is IPPA scale (parent attachment) and disciplinary scale. Hypothesis in this research is there is positive relation between parent attachment with student discipline. Data analysis was done by statistical technique from Product Moment from Pearson using SPSS 18.0 for windows. The result of data analysis show open coefficient (rxy) = 0,285 with significance level 0.000 (less than 0,01) accepted hypothesis. The results showed there was a positive relationship between parents with discipline students in MTs Nurul Huda Sedati.